Evaluation of silica-H2SO4 as an efficient heterogeneous catalyst for the synthesis of chalcones. - Sultan, Aeysha; Raza, Abdul Rauf; Abbas, Muhammad; Khan, Khalid Mohammed; Tahir, Muhammad Nawaz; Saari, Nazamid (MDPI, 2013)
We report an efficient silica-H2SO4 mediated synthesis of a variety of chalcones that afforded the targeted compounds in very good yield compared to base catalyzed solvent free conditions as well as acid or base catalyzed refluxing conditions.